ANALISIS PERBANDINGAN RASIO KEUANGAN ANTARA BANK KONVENSIONAL DAN BANK SYARIAH (STUDi KASUS PT BANK PANIN TBK DAN PT BANK PANIN DUBAI SYARIAH TBK PERIODE 2014-2016) - Rosmini, Rosmini; suarni, Agusdiwana (Universitas Muhammadiyah Makassar, 2019)
This study determines the differences in financial ratios between conventional banks and Islamic banks. The research method used is descriptive quantitative research and comparative methods. Secondary data is data obtained from companies in the form of data and documents at PT. Bank Panin Tbk and PT. Bank Panin Dubay Syariah Tbk. The samples used in this study were PT Bank Panin Tbk and PT bank Panin Dubai Syariah Tbk in 2014-2016. Based on the results of the analysis in this study, it is seen from the ratio of CAR, ROA, ROE, there are differences in financial ratios between conventional banks and Islamic banks. Judging from the percentage of financial ratios, conventional banks are better than Islamic banks. Islamic banks need to increase their ROA and ROE values because they are still below the standard set by Bank Indonesia, namely being careful in expanding their business. It is expected that every business expansion will generate profits and do not allow assets to grow without generating profits for the company.Keywords: Islamic Banking, Islamic Conventional, Bank Panin Syariah